Magnetic Materials: Experimental Evidence of Chiral Ferrimagnetism in Amorphous GdCo Films (Adv. Mater. 27/2018). Issue 27 (2nd July 2018) - Streubel, Robert; Lambert, Charles‐Henri; Kent, Noah; Ercius, Peter; N'Diaye, Alpha T.; Ophus, Colin; Salahuddin, Sayeef; Fischer, Peter
Abstract : Harnessing high‐resolution Lorentz microscopy, in article number1800199, Robert Streubel and co‐workers visualize chiral ferrimagnetic domain walls in amorphous films, revealing a composition dependence that potentially enables a temperature control of intrinsic domain wall properties. The reconstructed electron phase (magnetic induction) of achiral Bloch domain walls is shown here.